Guidelines for the integration of EMS based in ISO 14001 with Cleaner Production - Oliveira, José Augusto De; Oliveira, Otávio José De; Ometto, Aldo Roberto; Capparelli, Helena Freitas (Associação Brasileira de Engenharia de Produção, 2016)
Abstract This study aims to propose guidelines for the integration of the Environmental Management System (EMS) based on ISO 14001 with the Cleaner Production (CP). For this, a systematic review was applied and five case studies have been carried out in industrial companies with considerable environmental performance. Located in the state of São Paulo, the researched companies have got CP projects to ensure environmental and economic gains and shown prominent compatibilities with the EMS based on ISO 14001. The proposed guidelines were performed in three parts: the planning stage, the integration stage and the stage of evaluation and analysis. The main compatibilities include dissemination of the environmental culture, synergy between some specific requirements of the standard and the CP, as the general requirements, legal requirements, environmental policy, training, qualification and monitoring. The guidelines can increase operational efficiency and strategic environmental management in enterprises.
Keywords: Environmental Management System; ISO 14001; Cleaner Production; Integration; Brazilian industries